Relazioni affettive e frontiere giuridiche. Famiglia e famiglie nello spazio europeo tra fattore religioso, diritti nazionali e strategie di convergenza (Stato, Chiese e pluralismo confessionale, 2023)
Emotional relationships and legal border. Family and families in the European area from religious factors and national law to agreement strategiesABSTRACT: The family is subject to socio-cultural changes and it is regulated differently from European legal systems. In addition, in Europe, by fall of geographical barriers and the increase of migration, there has been the spread of family models not compatible with the principles and values of the host countries resulting in legal, cultural and religious conflicts. The movement of people within the European area call for coordinated actions and/or the adoption of adaptation techniques processes to the recognition of family status and related rights. This process aims to avoid that one legal relations with internationality may undergone different and heterogeneous regulatory disciplines with implications on the effective enjoyment of fundamental rights and religious ones. This work analyzes the regulation of family law in the European judicial area to understand which path to follow in preventing that the movement of people may be hampered by the heterogeneous of national laws and the relevance of the religious factor in this context.SOMMARIO: - 1. Brevi considerazioni introduttive - 2. La disciplina sostanziale del diritto di famiglia in Europa: la competenza degli ordinamenti nazionali. - 3. Famiglia e diritti nel sistema europeo - 4. Concetto di famiglia e diritto alla vita familiare - 5. Il diritto di famiglia e l’azione dell’Unione europea nello spazio di libertà, sicurezza e giustizia - 6. Sharīʿah, famiglia e diritto europeo: un rapporto difficile e controverso - 7. I Principles of European Family Law - 8. La famiglia tra diritto comune e politiche di armonizzazione - 9. In somma.